Respostas

2013-12-04T20:57:36-02:00
Vamos resolver pelo metodo de Adição :
 \left \{ {{2x + 5y=-3} \atop {3x - 4x=7}} \right.

\left \{ {{2x + 5y=-3 (.4)} \atop {3x - 4x=7(.5)}} \right

\left \{ {{8x + 20y=-12} \atop {15x - 20x=35}} \right 

23x = 23
x = 1
__________________________________________________
2x + 5y = - 3
2.1 + 5y = - 3
5y = - 3 - 2
5y = - 5
y = -1
 
1 5 1
A melhor resposta!
2013-12-04T20:58:23-02:00
 \left \{ {{2x+5y=-3~.(3)} \atop {3x-4y=7.(-2)}} \right.

 \left \{ {{6x+15y=-9} \atop {-6x+8y=-14}} \right. \\
\\23y=-23\\y=-23\div23\\y=-1

Substituindo na primeira :

2x+5y=-3\\
\\x= \frac{-3-5y}{2} \\
\\x= \frac{-3-5(-1)}{2} \\
\\x=1
3 5 3